Bark functional ecology: evidence for tradeoffs, functional coordination, and environment producing bark diversity. Issue 2 (7th October 2013) - Rosell, Julieta A.; Gleason, Sean; Méndez‐Alonzo, Rodrigo; Chang, Yvonne; Westoby, Mark
Summary The causes underlying bark diversity are unclear. Variation has been frequently attributed to environmental differences across sites. However, variation may also result from tradeoffs and coordination between bark's multiple functions. Bark traits may also covary with wood and leaf traits as part of major dimensions of plant variation. To assess hypotheses regarding tradeoffs and functional coordination, we measured bark traits reflecting protection, storage, mechanics, and photosynthesis in branches of 90 species spanning a wide phylogenetic and environmental range. We also tested associations between bark, wood, and leaf traits. We partitioned trait variation within species, and within and across communities to quantify variation associated with across‐site differences. We observed associations between bark mechanics and storage, density and thickness, and thickness and photosynthetic activity. Increasing bark thickness contributed significantly to stiffer stems and greater water storage. Bark density, water content, and mechanics covaried strongly with the equivalent wood traits, and to a lesser degree with leaf size, xylem conductivity, and vessel diameter. Most variation was observed within sites and had low phylogenetic signal. Compared with relatively minor across‐site differences, tradeoffs and coordination among functions of bark, leaves, and wood are likely to be major and overlooked factors shaping bark ecology and evolution.